Patient perceptions of copay card utilization and policies - Dimika Cavalier; Bridget Doherty; Gabrielle Geonnotti; Aarti Patel; Wesley Peters; Steven Zona; Lisa Shea (Journal of Market Access & Health Policy, 2023)
ABSTRACTBackground: Copay cards are intended to mitigate patient out-of-pocket (OOP) expenses. This qualitative, exploratory focus group study aimed to capture patient perceptions of copay cards and copay adjustment programs (CAPs; insurers’ accumulator and maximizer policies), which redirect the copay card utilization benefits intended for patients’ OOP expenses.Methods: Patients with chronic conditions were recruited through Janssen’s Patient Engagement Research Council program. They completed a survey and attended a live virtual session to provide feedback on copay cards.Results: Among 33 participants (median age, 49 years [range, 24–78]), the most frequent conditions were cardiovascular-metabolic disease and inflammatory bowel disease. Patients associated copay cards with lessening financial burden, improving general and mental health, and enabling medication adherence. An impact on medication adherence was identified by 10 (63%) White and nine (100%) Black respondents. Some patients were unaware of CAPs despite having encountered them; they recommended greater copay card education and transparency about CAPs.Conclusion: Patients relied on copay cards to help afford their prescribed medication OOP expenses and maintain medication adherence. Use of CAPs may increase patient OOP expenses. Patients would benefit from awareness programs and industry – healthcare provider partnerships that facilitate and ensure access to copay cards.